Metathesis of 9-octadecenoic acid methyl ester: diversity and mechanism of product formation at various Grubbs’ catalyst concentrations - Vyshnavi, Yelchuri; Prasad, Rachapudi Badari Narayana; Karuna, Mallampalli Sri Lakshmi (European Journal of Chemistry, 2015)
Self-metathesis of 9-octadecenoic acid methyl ester was carried out with varying the concentration of Grubbs’ second generation catalyst from 0.03 mmol to 0.18 mmol at 40-45 °C for 36 h. Only two products (9-octadecene 30%, and dimethyl-9-octadecene-dienoate 23%) resulted when 0.06 mmol of catalyst was employed, while at other concentrations four metathesized products were observed. 9-Octadecene generated at 0.03, 0.06 and 0.12 mmol completely disappeared and dimethyl-9-octadecene-dienoate (64%) was observed in major amounts at 0.18 mmol concentration.